Safety and effectiveness of appropriately and inappropriately dosed rivaroxaban or apixaban versus warfarin in patients with atrial fibrillation: a cohort study with nested case–control analyses from UK primary care - Luis Alberto García Rodríguez; Pareen Vora; Luke Roberts; Gunnar Brobert; Samuel Fatoba; María Eugenia Sáez; Antonio González-Pérez (BMJ Open)
Objectives To investigate effects of appropriately and inappropriately dosed apixaban/rivaroxaban versus warfarin on effectiveness and safety outcomes in patients with non-valvular atrial fibrillation (NVAF).Design Cohort study with nested case–control analyses using primary care electronic health records (IQVIA Medical Research Data UK database).Setting UK primary care.Participants Patients aged ≥18 years with NVAF newly prescribed apixaban (N=14 701), rivaroxaban (N=14 288) or warfarin (N=16 175) between 1 January 2012 and 30 June 2018, and followed up to 31 December 2018.Primary and secondary outcome measures Incident cases of ischaemic stroke/systemic embolism (IS/SE) and intracranial bleeding (ICB). Cases were matched to controls on age, sex and OAC naïve status. Using logistic regression, adjusted ORs with 95% CIs were calculated for the outcomes comparing apixaban/rivaroxaban use (appropriate or inappropriate dosing based on the product label criteria) and warfarin.Results For IS/SE, ORs (95% CIs) for apixaban versus warfarin were 1.19 (0.92–1.52) for appropriate dose and 1.01 (0.67–1.51) for inappropriate dose; for rivaroxaban versus warfarin, estimates were 1.07 (0.83–1.37) for appropriate dose and 1.21 (0.78–1.88) for inappropriate dose. For ICB, ORs (95% CIs) for apixaban versus warfarin were 0.67 (0.44–1.00) for appropriate dose and 0.45 (0.21–0.95) for inappropriate dose; for rivaroxaban versus warfarin, estimates were 0.81 (0.55–1.20) for appropriate dose and 1.14 (0.56–2.31) for inappropriate dose.Conclusions Dosing appropriateness in NVAF was not associated with a significant difference in IS/SE risk or increase in ICB risk versus warfarin. These findings may reflect residual confounding and biases that were difficult to control, as also seen in other observational studies. They should, therefore, be interpreted with caution, and prescribers should adhere to the dosing instructions in the respective Summary of Product Characteristics. Further studies on this topic from real-world populations are needed.